Fiscal Policy, Interest Rate Spreads, and the Zero Lower Bound - Christian Bredemeier; Falko Juessen; Andreas Schabert (Institute for the Study of Labor (IZA), 2015)
This paper questions unconventional fiscal policy effects when the monetary policy rate is at the zero lower bound. We provide evidence for the US that the spread between the policy rate and the US-LIBOR, which is more relevant for private sector transactions, increases with government expenditures. We introduce a corresponding spread into an otherwise standard macroeconomic model which reproduces this observation. The model predicts that the fiscal multiplier takes conventional values, regardless of whether the policy rate follows a standard feedback rule or is at its zero lower bound. Likewise, labor tax increases exert contractionary effects in both cases.
Keywords: E32; E42; E63; 330; fiscal multiplier; tax policy; interest rate spreads; zero lower bound; liquidity premium